2019
DOI: 10.35741/issn.0258-2724.54.5.34
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles Using the UV-Irradiation Technique in an Antibacterial Application

Abstract: The article describes a new way to the synthesis of silver nanoparticles based on UV-irradiation energy. Our technique allows for producing high quality and clean nanoparticles. Moreover, our photolysis approach allows us to synthesis silver nanoparticles (Ag NPs) with very low cost and short time. The nanostructures were characterized using X-ray diffraction, transmission electron spectroscopy and UV-visible spectrometer. Most of the Ag NPs are shown to be a hexagonal shape and some of them are a spherical sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The maximum power can be calculated from relationship (1). The fill factor is a substantial parameter that can be calculated from relationship (2), which defines the power conversion efficiency of the solar cellthe conversion efficiency is the ratio between the maximum electrical power coming out and the falling photovoltaic power, which can be calculated as in the relationship (3). There are numerous factors that can significantly influence (F.F.…”
Section: B Fill Factor and Conversion Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum power can be calculated from relationship (1). The fill factor is a substantial parameter that can be calculated from relationship (2), which defines the power conversion efficiency of the solar cellthe conversion efficiency is the ratio between the maximum electrical power coming out and the falling photovoltaic power, which can be calculated as in the relationship (3). There are numerous factors that can significantly influence (F.F.…”
Section: B Fill Factor and Conversion Efficiencymentioning
confidence: 99%
“…The best fill factor and conversion efficiency was achieved when using nano L1Ag. Pm = Vm * Im (1)F.F = Pm/V OC * I SC (2) η = (Pm/R*A)×100 (3) (1) Table 4. Solar cell parameters of dye sensitizer solar cell for (Ag/nanoL1Ni/silicon/Al, Ag/nanoL1Ag/silicon/Al, Ag/nanoL1Pd/silicon/Al) and (Ag/L1Ni /silicon/Al, Ag/L1Ag/silicon/Al, Ag/L1Pd/silicon/Al)…”
Section: B Fill Factor and Conversion Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…TMCs drugs (TMCD) have become increasingly important in inorganic and medicinal chemistry and have attracted a great deal of attention over the past decade in drug development strategies [4,5]. The studies have also shown that the nanomaterials and nanocomplexes have distinctive physical, chemical and biological applications [6][7][8][9][10][11][12][13][14][15][16][17]. Theophylline, 1,3-dimethylxanthine, with significant biological characteristics, is a purine alkaloid.…”
Section: Introductionmentioning
confidence: 99%
“…Nanochemistry is one of the modern sciences that has many applications [1], [2], [3], [4], [5]. It is known that nanosized metal composites has different chemical, physical, and optical properties than for their bulky sized composites, which is due to their composition dependent properties, and these advanced properties can give materials designs that offer many advantages in the communication industry.…”
Section: Introductionmentioning
confidence: 99%